Smarthome Design Using Raspberry Pi 3 Based on Internet Of Things (IoT) - Putra, Urief Arsani Atma; Syamsul Irfan Akbar, L Ahmad; Ramadhani, Cipta (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2025)
Advances in Internet of Things (IoT) technology have driven the development of smart, efficient, and widely accessible home automation systems. This study aims to determine how to design and integrate Raspberry Pi technology with Bylnk to control relays remotely manually using widgets and automatically using LDR and DHT11 sensors. The research method employs an engineering research approach focused on the design, development, and testing of a prototype smart home system based on the Internet of Things (IoT) using Raspberry Pi 3. The process begins with a literature review on IoT concepts and Raspberry Pi characteristics, followed by the design of hardware and software that integrates the Raspberry Pi 3, LDR and DHT11 sensors, a four-channel relay module, and the Blynk platform for the user interface. After assembly, the system is tested through experimental scenarios observing LED responses to four input conditions: light intensity, ambient temperature, automatic timer, and manual commands via the Blynk app. The collected data is quantitative observational, including LED status (on/off), response time, and analyzed descriptively and comparatively by comparing actual results against the success criteria established in the design. The test results show that the system operates reliably in executing each control function, both automatic and manual, with fast and accurate responses. This research contributes to the development of a modular, cost-effective, and easily implementable smart home system in real residential environments.